Моделі та механізми управління проектами морських транспортних перевезень = Models and mechanisms of management of maritime transportations projects - Pokotilov, I. P.; Покотілов, Ігор Пилипович (My University, 2012)
Робота присвячена удосконаленню методології, моделей та механізмів управління проектами МТП. Розкриті основні концепції і категоріальний апарат МТП. Проаналізовано склад морського флоту і стан міжнародних МТП. Визначені принципові підходи і чинники впливу на стан проектів МТП. Проведений аналіз міжнародного досвіду управління проектами МТП і встановлені чинники, які стримують розвиток МТП в Україні = It is uncovered the basic concepts and categorical apparatus maritime transportation of cargo. It is defined principal approaches and effects on the marine transport. It is given characteristic substantive areas and is created a conceptual framework project cycle of maritime cargo transportation. It is presented the methodology design of typical technological processes for automated control systems. It is represented the phased modelling methodology of Information System, information business processes in projects maritime transportation of cargo. It is formulated and reviewed stages of system design.
Покотілов, І. П. Моделі та механізми управління проектами морських транспортних перевезень : автореф. дис. ... канд. техн. наук : 05.13.22 / І. П. Покотілов ; НУК ; наук. кер. К. В. Кошкін. - Миколаїв, 2012. - 20 с. + ел. копія.
Keywords: управління проектами; морські транспортні перевезення; когнітивне моделювання; сценарії ефективних перевезень; project management; maritime transportation of cargo; cognitive modelling; effective transportation scenario